2016
DOI: 10.1038/ncomms11220
|View full text |Cite
|
Sign up to set email alerts
|

Explosive cell lysis as a mechanism for the biogenesis of bacterial membrane vesicles and biofilms

Abstract: Many bacteria produce extracellular and surface-associated components such as membrane vesicles (MVs), extracellular DNA and moonlighting cytosolic proteins for which the biogenesis and export pathways are not fully understood. Here we show that the explosive cell lysis of a sub-population of cells accounts for the liberation of cytosolic content in Pseudomonas aeruginosa biofilms. Super-resolution microscopy reveals that explosive cell lysis also produces shattered membrane fragments that rapidly form MVs. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

31
630
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 549 publications
(664 citation statements)
references
References 69 publications
(121 reference statements)
31
630
1
2
Order By: Relevance
“…In the Pseudomonas literature, AQs are generally presented to contain 7-Carbon (C7) side chains (HHQ, PQS, and HQNO), yet 9-Carbon (C9; NHQ, C9-PQS, and NQNO) and 11-Carbon (C11; UHQ, C11-PQS, and UQNO) side chain variants of these molecules are also common (16,17). The extracellular presence of PQS in P. aeruginosa communities is attributed to packaging and transport in outer membrane vesicles (OMVs) (28,29), yet cell lysis could also contribute to their release (30).…”
Section: Introductionmentioning
confidence: 99%
“…In the Pseudomonas literature, AQs are generally presented to contain 7-Carbon (C7) side chains (HHQ, PQS, and HQNO), yet 9-Carbon (C9; NHQ, C9-PQS, and NQNO) and 11-Carbon (C11; UHQ, C11-PQS, and UQNO) side chain variants of these molecules are also common (16,17). The extracellular presence of PQS in P. aeruginosa communities is attributed to packaging and transport in outer membrane vesicles (OMVs) (28,29), yet cell lysis could also contribute to their release (30).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover and importantly, these giant rounded cells were observed for up to 6 h of culture and never lysed. Conversely, once formed, 86% of large rounded Pseudomonas cells survive for <60 s before lysing (36). The limited (if any) bacterial cell death and absence of explosive cell lysis under the culture conditions we tested suggested that the observed release of eDNA and associated DNABII proteins from NTHI very early in biofilm formation likely occurred via an alternative nonlytic mechanism.…”
Section: Resultsmentioning
confidence: 91%
“…For clarity, additional experiments were conducted with a viability stain to confirm this assertion. We next determined whether altruistic cell death by explosive cell lysis facilitated the observed deposition of DNA, as is described for Pseudomonas (36). Although a small number (<1 for every 1,000 cells) of NTHI did indeed form giant rounded cells similar in morphology to those described for Pseudomonas, these rounded cells did not form until much later in time [e.g., more than 3 h after inoculation compared with ≤1 h after incubation as reported for Pseudomonas (36)].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations